Reviewing the EBSA process: Improving on success. (February 2018) - Johnson, David E.; Barrio Froján, Christopher; Turner, Phillip J.; Weaver, Philip; Gunn, Vikki; Dunn, Daniel C.; Halpin, Patrick; Bax, Nicholas J.; Dunstan, Piers K.
Abstract: This paper reviews key aspects of the implementation of the Convention on Biological Diversity's Ecologically or Biologically Significant Area (EBSA) process to date, anticipating global marine coverage of that process in so far as is possible by the end of 2018. EBSAs merge marine and coastal physical, biological and biogeographical information held by States, diverse scientific institutions and individual experts to identify inherent value of marine biodiversity, as well as providing a focus for either States or international organisations with sectoral competences to apply potential management measures to protect and sustainably manage biodiversity. In assessing information made available at dedicated EBSA Regional Workshops, several common patterns emerged, both in the data made available and in the gaps in information. The latter include missing information, representation of taxa and features of interest, and specialist expertise. The review exercise detailed here has highlighted the value and efficacy of the EBSA process and the information it has generated, despite some recognised shortcomings. It further suggests that there is potential to strengthen the EBSA portfolio by (i) adding some selected new areas yet to be described, (ii) revisiting existing EBSAs to add both new and existing information, and (iii) reconsidering some areas previously deemed to not meet the EBSA criteria by incorporating both new and existing information. Improving the systematic assessment of areas against the EBSA criteria could be achieved using a combination of (i) spatially precise systematic conservation approaches, supported by (ii) predictive modelling and biogeographic multi-criteria approaches based on expert judgement. Highlights: The CBD's process of describing Ecologically or Biologically Significant Areas (EBSAs) has reached a critical juncture. EBSAs may require appropriate management interventions to maintain critical natural capital. Gap analysis highlights scope to add information, taxa and features of interest, and additional specialist expertise. Opportunities to strengthen the utility of EBSAs include adding new data, involving new expertise and addressing omissions. Best available, regularly updated information is needed to keep EBSAs relevant.